2014
DOI: 10.1097/pgp.0b013e3182988dfd
|View full text |Cite
|
Sign up to set email alerts
|

Stage IIIC Ovarian/Peritoneal Serous Carcinoma

Abstract: Primary ovarian serous carcinoma patients presenting with regional lymph node metastasis without extrapelvic peritoneal metastasis are considered International Federation of Gynecology and Obstetrics (FIGO) Stage IIIC. We studied their controversial survival compared with patients with extrapelvic peritoneal metastasis in same Stage IIIC. We included primary peritoneal carcinoma patients with lymph node metastasis to investigate whether primary site of tumor has a prognostic role. Charts of patients treated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…These group of patients showed significant best OS in our study (table 4), as described in one report that ovarian serous carcinoma patients with sole extrapelvic peritoneal involvement have better survival than those with extrapelvic peritoneal involvement and lymph node metastases 11. Additionally, an adequate staging is possible by performing a lymphadenectomy 5.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These group of patients showed significant best OS in our study (table 4), as described in one report that ovarian serous carcinoma patients with sole extrapelvic peritoneal involvement have better survival than those with extrapelvic peritoneal involvement and lymph node metastases 11. Additionally, an adequate staging is possible by performing a lymphadenectomy 5.…”
Section: Discussionsupporting
confidence: 77%
“…All surgical pathologic samples were examined by a gynecological pathologist. The histological diagnosis was classified according to FIGO- stages 11. Residual tumor mass was subdivided in the following groups: R0 = complete cytoreduction (=0mm) and R>0mm- ≤10mm.…”
Section: Material/ Methodsmentioning
confidence: 99%
“…It has been also suggested that Stage IIIC in previous FIGO stage may be consisted of heterogeneous groups [ 5 ]. The most important issue that has been raised is the differences in prognosis between stage IIIC with intra-abdominal metastasis and IIIC with isolated lymph node metastasis without coelomic metastasis which is reported to be associated with better prognosis [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical exploration and pathological staging is standard procedure for classification of EOC and International Federation of Gynecology and Obstetrics (FIGO) classification is widely used. However, there have been debates on the issues that existing FIGO staging of EOC classifies heterogeneous groups of population as same stage [ 5 , 6 ]. For example, FIGO stage IIIC patients with only isolated lymph node metastasis have been shown better prognosis compared to the patients with stage IIIC with peritoneal carcinomatosis or abdominal metastatic lesion more than 2 cm [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Less than 10% of ovarian carcinomas extend beyond the pelvis with exclusively retroperitoneal lymph node involvement. Evidence in the literature indicates that these cases have a better prognosis than that of tumors with abdominal peritoneal involvement [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The new staging includes a revision of stage III patients and assignment to stage IIIA1 based on spread to the retroperitoneal lymph nodes without intraperitoneal dissemination.…”
Section: Main Changesmentioning
confidence: 99%